2017
DOI: 10.1038/s41598-017-14892-x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of mRNA Sequencing with Random Primed and 3′-Directed Libraries

Abstract: Creating a cDNA library for deep mRNA sequencing (mRNAseq) is generally done by random priming, creating multiple sequencing fragments along each transcript. A 3′-end-focused library approach cannot detect differential splicing, but has potentially higher throughput at a lower cost, along with the ability to improve quantification by using transcript molecule counting with unique molecular identifiers (UMI) that correct PCR bias. Here, we compare an implementation of such a 3′-digital gene expression (3′-DGE) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 33 publications
(27 reference statements)
4
44
0
Order By: Relevance
“…4B). A similar tendency was observed in a previous study on comparison of 3′mRNA-Seq and a conventional RNA-Seq 33 . For genes with relatively low expression, higher expression was detected by the conventional method than by Lasy-Seq, which might have been caused by the difference in distribution of reads within gene bodies between RNA-Seq with oligo-dT RT primer (3′mRNA-Seq, including Lasy-seq) and random RT-primer (conventional method) ( Fig.…”
Section: Comparison Of Quantitative Performance Of a Conventional Metsupporting
confidence: 89%
See 1 more Smart Citation
“…4B). A similar tendency was observed in a previous study on comparison of 3′mRNA-Seq and a conventional RNA-Seq 33 . For genes with relatively low expression, higher expression was detected by the conventional method than by Lasy-Seq, which might have been caused by the difference in distribution of reads within gene bodies between RNA-Seq with oligo-dT RT primer (3′mRNA-Seq, including Lasy-seq) and random RT-primer (conventional method) ( Fig.…”
Section: Comparison Of Quantitative Performance Of a Conventional Metsupporting
confidence: 89%
“…4C). A previous study reported that www.nature.com/scientificreports www.nature.com/scientificreports/ the number of detected genes and the differentially expressed genes (DEGs) became larger in the conventional method with random RT primer than in the RNA-Seq with oligo-dT RT primer (3′mRNA-Seq) 33 . Also, in our comparison of the two methods, a larger number of genes and DEGs between light and dark conditions were detected in the conventional method than in Lasy-Seq (Fig.…”
Section: Comparison Of Quantitative Performance Of a Conventional Metmentioning
confidence: 99%
“…Total RNA was extracted using TRIzol (Life Technologies, Cat: 15596018) per manufacturer instructions (detailed SOP at www.dtoxs.org ; DToxS SOP A– 1.0: Total RNA Isolation). RNA sequencing and analysis was performed as previously described [ 83 ]. We prepared RNA-seq libraries by adapting a single-cell RNA-seq technique—Single Cell RNA Barcoding and Sequencing method (SCRB-seq; [ 84 , 85 ])—to extract total RNA from cells (detailed SOP at www.dtoxs.org ; DToxS SOP A– 6.0: High-throughput mRNA Seq Library Construction for 3' Digital Gene Expression (DGE)).…”
Section: Methodsmentioning
confidence: 99%
“…Combinatorial therapies have been suggested as a crucial approach to addressing such intratumor heterogeneity and associated treatment response (30,31,83). Emerging single-cell analytical tools, such as single-cell transcriptomics, are thus of great interest for their potential to support development of combinatorial therapies (84)(85)(86). For instance, single-cell phosphoproteomic profiling allowed the characterization of signaling dynamics and the selection and validation of combination therapies for a glioblastoma in vivo model (86).…”
Section: Systems-level Measurement Of Combinatory Drug Interactionsmentioning
confidence: 99%